2017
DOI: 10.1161/atvbaha.117.309374
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of Inflammatory Processes in Atherosclerosis and Its Complications

Abstract: Physiological cardiovascular functions show daily diurnal variations, which are synchronized by intrinsic molecular clocks and environment-driven cues. The clinical manifestation of cardiovascular disease also exhibits diurnal variation, with an increased incidence in the early morning. This coincides with circadian oscillations of circulating parameters, such as hormones and leukocyte counts. We are just at the beginning of understanding how circadian rhythms of immune functions are related to cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Accordingly, the effect of anaesthesia nearer to bedtime21 22 as well as the negative role of a longer fasting for patients operated on in the later hours19 23 have also been suggested as possible factors influencing patients’ heart recovery. Also, cell-intrinsic clocks sensible to proinflammatory stimuli, such as a surgical procedure, have been characterised in macrophages and other inflammatory cell lines involved in atherosclerotic plaque stability,24 possibly impacting on the risk of AMI in the follow-up depending on the time of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the effect of anaesthesia nearer to bedtime21 22 as well as the negative role of a longer fasting for patients operated on in the later hours19 23 have also been suggested as possible factors influencing patients’ heart recovery. Also, cell-intrinsic clocks sensible to proinflammatory stimuli, such as a surgical procedure, have been characterised in macrophages and other inflammatory cell lines involved in atherosclerotic plaque stability,24 possibly impacting on the risk of AMI in the follow-up depending on the time of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for discrepancies between studies could be due to model-specific factors (e.g., rodent strain, type of exercise) or differences in cardiac perfusion protocols (e.g., substrate levels, addition of hormones). Circadian rhythm may also account for disparate findings because it influences cardiac metabolism ( 218 ), stress responses and protein turnover ( 219 ), and inflammatory processes ( 220 ). Chronobiology remains an important consideration for understanding how exercise influences cardiac biochemistry and physiology ( 221 , 222 ).…”
Section: How Does Cardiac Metabolism Change During Exercise?mentioning
confidence: 99%
“…Nocturnal shiftwork alters the rhythmicity of the immune system, and such a disruption might play a role in the increased infection risk and higher incidence of autoimmune diseases, cancer, and cardiovascular and metabolic disorders (Esquirol et al, 2011 ). It has been suggested that the increase in artificial light exposure in modern societies parallels the increase in obesity prevalence, with altered circadian homeostasis clearly contributing to cardiovascular and metabolic derangements (Versteeg et al, 2016 ; Kiehn et al, 2017 ; Mayeuf-Louchart et al, 2017 ; Steffens et al, 2017 ; Tarquini and Mazzoccoli, 2017 ). Shift work, especially night work and long working hours are among the possible modifiable risk factors that influence the incidence of cardiovascular and metabolic risk factors (Puttonen et al, 2010 ; Nabe-Nielsen et al, 2017 ) and sleep (Sallinen and Kecklund, 2010 ; McHill et al, 2014 ; Givens et al, 2015 ; Wirth et al, 2017 ; Wyse et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%